2020
DOI: 10.1186/s12904-020-00665-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing of a question prompt list to improve communication about the heart failure trajectory in patients, families, and health care professionals

Abstract: Background The aim of this study was to optimize a Question Prompt List which is designed to improve communication about the heart failure trajectory among patients, family members, and health care professionals. Methods Data were collected in a two-round Delphi survey and a cross-sectional survey, including patients with heart failure, their family members, and health care professionals working in heart failure care in Sweden and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
1
10
0
2
Order By: Relevance
“…This paper provided further insight into the challenges health care professionals experience in discussing the HF trajectory, including prognosis and end-of-life in HF care. We also found that using a communication tool such as a QPL was perceived by health care professionals as promising and useful, which also was supported by our previous research [2,13]. A recent publication described the experiences with a pre-visit QPL to determine the educational needs of patients with HF and their family members.…”
Section: Discussionsupporting
confidence: 80%
“…This paper provided further insight into the challenges health care professionals experience in discussing the HF trajectory, including prognosis and end-of-life in HF care. We also found that using a communication tool such as a QPL was perceived by health care professionals as promising and useful, which also was supported by our previous research [2,13]. A recent publication described the experiences with a pre-visit QPL to determine the educational needs of patients with HF and their family members.…”
Section: Discussionsupporting
confidence: 80%
“…The approach in the control of physical symptoms was the category most frequently addressed in the studies that make up this integrative review. [21][22][23]25,[27][28][29][30][31][32] For the relief of symptoms, it is necessary first to recognize them and understand how they affect the patient's routine. To make this assessment, one can make use of symptom assessment instruments, such as the Edmonton Symptom Assessment Scale (ESAS).…”
Section: Approach To Symptom Control and Promotion Of Comfort And Wel...mentioning
confidence: 99%
“…However, articulating this dimension with the integral approach and family orientation heightens the promotion of better quality of life while dealing with the disease. 21,[25][26][27][28][29][30][31][32]34 Nurses' practices also included the creation of dialog spaces to listen to what patients and family members have to say, to actively listen to their fears, their anxieties, and to help them free themselves from these feelings that can cause anxiety and depression. Spiritual issues approaches are part of the care practices implemented by nurses during the longitudinal follow-up of people with HF in palliative care.…”
Section: Comprehensiveness Of Family Care and Guidancementioning
confidence: 99%
“…Die am besten untersuchte Checkliste, die sogenannte Question Prompt List (QPL), enthält eine Reihe von Fragen, die während einer Konsultation verwendet werden können, um sicherzustellen, dass schwierige Themen in die Diskussion zwischen Patient*in, Familie, Betreuer*in und medizinischem Fachpersonal einbezogen werden [12]. Themenschwerpunkte umfassen u. a. den Einfluss der HF auf den Alltag, Unterstützungsmöglichkeiten bei Verschlechterung, HF am Lebensende, Fragen unter Einbezug der Angehörigen, Fragen für Patient*innen mit Schrittmacher/ICD (s. ▶ Tab.…”
Section: Frageaufforderungslisten (Qpl) Zur Gesprächsführung In Der A...unclassified